Comparison of Speech Therapist Training in Hungary and Austria (Training and Practice : Journal of Educational Sciences, 2016)
With entering the European Union students have more opportunities to do all or part of their studies abroad. The interoperability between the education systems and accepting each other’s degrees make it easy for them to study and work in a foreign country. The essay aims to introduce the structure and the possibilities of studying speech therapy in Austria and in Hungary. These can be bachelor and master studies, post-graduate and further education opportunities.